The Association Between Vitamin D Receptor Gene FokI Polymorphism and Pulmonary Tuberculosis - Dina Octafrida Marpaung; Bintang Yinke Magdalena Sinaga; Parluhutan Siagian; Erna Mutiara (Respiratory Science, 2021)
Backgrounds: There is a wide range of individual responses to mycobacterium infection. However, the reason why certain people suffers from a disease when they are infected with mycobacterium while others remain healthy is still unknown. Genetic susceptibility is thought to be one of the important explanatory factors for individuals with the risk of developing pulmonary tuberculosis (TB). FokI polymorphism was one of the genetic variations within the vitamin D receptor (VDR) gene associated with pulmonary TB. In the present study, we investigated the association between VDR gene FokI polymorphism and pulmonary TB. Conclusion: There was no significant association between the VDR gene FokI polymorphism and pulmonary TB.